中国上市公司治理结构研究 = On cooperation of listed companies in P.R.C. - 田军Tian, Jun (2008)
This study is focused on listed companies governing structures. Based on findings from empirical research, companies governing system reforms are important for establishing modern enterprises, improving listed companies quality, and increasing enterprises competition.